Photonic-Assisted Spintronic Solid-State Switching Model for High-Speed Memory Devices - Bibhu Prasad Ganthia; Rosalin Pradhan (International Journal of Solid State Innovations & Research, 2026)
The rapid advancement of high-speed computing and data-centric applications has intensified the demand for energy-efficient and ultra-fast memory technologies. This paper proposes a Photonic-Assisted Spintronic Solid-State Switching Model for next-generation high-speed memory devices. The proposed framework integrates photonic excitation mechanisms with spintronic switching dynamics to enhance data transfer speed, minimize switching delay, and reduce power dissipation in solid-state memory architectures. By combining optical pulse-assisted spin polarization with magnetic tunnel junction-based switching, the model achieves improved switching stability and enhanced thermal reliability under high-frequency operational conditions. The study employs a hybrid analytical and simulation-driven approach to evaluate switching efficiency, propagation latency, spin coherence retention, and energy consumption characteristics. Experimental modelling demonstrates that the proposed photonic-assisted architecture significantly outperforms conventional CMOS-based memory switching systems in terms of access speed, energy efficiency, and scalability. Furthermore, the integration of photonic control signals reduces electromagnetic interference and improves operational accuracy for high-density memory applications. The proposed model offers promising potential for future artificial intelligence processors, neuromorphic computing systems, quantum-inspired storage architectures, and ultra-fast embedded electronic platforms requiring reliable and low-power memory operation. For next-generation nanoelectronics memory systems operating in high-speed and energy-constrained computational environments with enhanced reliability and long-term operational stability, the suggested architecture supports scalable implementation, improves switching synchronisation, and strengthens signal integrity.
Keywords: Energy-Efficient Computing; High-Speed Memory; Magnetic Tunnel Junction; Photonic Switching; Solid-state devices; Spintronic Memory